Komunikasi Simbolik Dalam Proses Adat Poriwanga Pada Masyarakat Desa Rombo Kecamatan Kulisusu Kabupaten Buton Utara - didin, didin; Umran, La Ode Muhammad; Reskiawaty, Siti Utami (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2020)
ABSTRACTThe purpose of this study was to find out how the symbolic communication in the process of adat adat of the people in the village of Rombo and how the values contained in the traditional ceremony of the Chinese Traditional Culture in the village of Rombo Kec. Kulisusu North.Buton Regency. Using symbol theory and research methods used are qualitative research methods with 6 informants. The technique for determining informants in this study is the purposive sampling technique. While the data collection techniques used are observation, interviews, literature study and documentation. The results of this study indicate that prior to the implementation time is preceded by deliberations conducted by traditional leaders, religious leaders, community leaders and the head of Rombohal Village aims to discuss the time implementation and all preparations as well as determining a good day in the organization of the adat ceremony of pejwanga. After the implementation of the time determination, the village ofÂ  Rombo carried out perahangia, the perahangia activity was the final process of the Poriwanga custom before entering the implementation stage of the Poriwanga ceremony. After the implementation of the traditional ceremony ceremony, the community's community ceremony in Rombo Village carried out the process of the traditional ceremony that began with several celebrations such as Pomaani dance, Pangaru dance, Haroa (reading prayers and eating together), Lense dance, Ngibi dance and foreign danceKeywords: Communication;Symbolic;Ceremony;Poriwanga.